Acute metabolic complications of diabetes mellitus in a tertiary care center - Hanumanthaiah, Ramesh Gorghatta; Bangalore Krishnap, Panchakshari Prasanna; Prasad, Dheemantha; Farahat, Sheerin; T. S., Ranganath (International Journal of Advances in Medicine, 2017)
Background:Diabetes mellitus (DM) is a chronic medical disorder characterized by hyperglycemia. It arises due to inability of pancreas to produce insulin, either because of impaired insulin secretion, impaired action or both. Most of the untreated or inadequately treated patients develop acute metabolic complications. These complications are associated with high mortality and morbidity. Most common among the acute metabolic complications are diabetic ketoacidosis (DKA), hyperglycemic, hyperosmolar, non-ketotic state (HHNKS), Lactic acidosis (LA) and hypoglycemia. Early diagnosis and management of DM helps in preventing these complications. This study was aimed to determine the incidence of acute metabolic complications in DM and to determine the distribution of age and sex in different metabolic complications of diabetes mellitus. Methods: A prospective study was conducted on all cases presenting to Emergency Medicine department for a period of one year from April 2014 to March 2015. Results:Out of the 1211 cases 632 were Diabetic ketoacidosis, 329 cases were hypoglycemia, 201 cases were hyperglycemic hyperosmolar nonketotic state, 12 cases were lactic acidosis. The other 37 cases had findings which were overlapping with more than one type of acute metabolic complications related to diabetes mellitus. Two cases of HHNKS were associated with attacks of hypoglycemia. In this study, diabetic ketoacidosis was the common acute metabolic complication affecting Males aged less than 15 years. Conclusions:Hypoglycemia is the commonest iatrogenic acute metabolic complications India diabetes mellitus. HHNKS affects patients aged more than 45 years. In some cases, there is considerable overlap of diabetic ketoacidosis, lactic acidosis, hypoglycemia and HHNKS.